2006
DOI: 10.1038/sj.ijo.0803298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of a 17q chromosomal region linked to obesity phenotypes in the IRAS family study

Abstract: Objective: Obesity is widely accepted to be influenced by both environmental and genetic factors. Several recent studies have used the positional cloning approach in an attempt to discover genes contributing to obesity. In the IRAS Family Study a genomewide scan was performed on 1425 individuals of Hispanic descent (90 extended pedigree families) to identify regions of the genome linked to obesity phenotypes. Methods: Nonparametric QTL linkage analysis was performed using a variance components approach. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…However, supporting our results, a genome-wide scan carried out in the Insulin Resistance Atherosclerosis Study (IRAS) family study [10] identified the region on chromosome 17q, where the SSTR2 gene is located, with evidence of linkage to visceral adipose tissue, waist circumference and BMI. Some years later [16] , researchers of the IRAS family study investigated the influence of 10 polymorphisms at the SSTR2 locus on insulin resistance.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, supporting our results, a genome-wide scan carried out in the Insulin Resistance Atherosclerosis Study (IRAS) family study [10] identified the region on chromosome 17q, where the SSTR2 gene is located, with evidence of linkage to visceral adipose tissue, waist circumference and BMI. Some years later [16] , researchers of the IRAS family study investigated the influence of 10 polymorphisms at the SSTR2 locus on insulin resistance.…”
Section: Discussionsupporting
confidence: 63%
“…Its gene is located in 17q24 and the SSTR2 gene is the one that contains at least 1 intron, in contrast to other members of the somatostatin receptor family that are intronless [9] . In a genome-wide scan [10] , performed on 1,425 individuals of Hispanic descent to identify regions of the genome linked to obesity phenotypes, evidence for linkage to obesity traits was observed at 17q. Additional fine mapping identified the SSTR2 gene as a positional candidate for obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the actions of central and peripheral galanin and its receptors in the regulation of metabolism, obesity, and appetite, including galanin receptor-linked mechanisms in experimental obesity, were recently reviewed in detail (Fang et al, 2012a), with the authors recommending development of GAL 1 antagonism as a novel antiobesity strategy. However, in early clinical studies, there was no strong association reported between GAL or GAL 1 genetic variants and obesity or dietary fat intake in obese children and adolescents (Schauble et al, 2005) and no evidence for a GAL 2 linkage to obesity (Sutton et al, 2006) (Table 6). …”
Section: Obesitymentioning
confidence: 99%
“…Indeed, despite the widely reported and diverse effects of galanin on consummatory behavior, genetic linkage studies have to date revealed no strong impact of the galanin or galanin receptor genes on obesity Lapsys et al, 1999;Schauble et al, 2005;Sutton et al, 2006; section VII.C). However, it has become clear over recent years that common neural circuits can be involved in mediating different behaviors such as the regulation of feeding and fear/ anxiety.…”
Section: A Feeding and Energy Homeostasismentioning
confidence: 99%
“…These participants were from 80 different families with an average family size of 12. In prior years extensive linkage analysis studies were performed (Rich, 2004;Sutton, 2006;Palmer 2006). Especially notable for the strength of the linkage evidence was analysis of the adipocytokine adiponectin, coded for by the ADIPOQ gene (Guo, 2006).…”
Section: Combining Exome Sequencing With Linkage Analysismentioning
confidence: 99%